Organic complexation of U(VI) in reducing soils at a natural analogue site: Implications for uranium transport. (September 2020) - Fuller, Adam J.; Leary, Peter; Gray, Neil D.; Davies, Helena S.; Mosselmans, J. Frederick W.; Cox, Filipa; Robinson, Clare H.; Pittman, Jon K.; McCann, Clare M.; Muir, Michael; Graham, Margaret C.; Utsunomiya, Satoshi; et al.
Abstract: Understanding the long-term fate, stability, and bioavailability of uranium (U) in the environment is important for the management of nuclear legacy sites and radioactive wastes. Analysis of U behavior at natural analogue sites permits evaluation of U biogeochemistry under conditions more representative of long-term equilibrium. Here, we have used bulk geochemical and microbial community analysis of soils, coupled with X-ray absorption spectroscopy and μ-focus X-ray fluorescence mapping, to gain a mechanistic understanding of the fate of U transported into an organic-rich soil from a pitchblende vein at the UK Needle's Eye Natural Analogue site. U is highly enriched in the Needle's Eye soils (∼1600 mg kg −1 ). We show that this enrichment is largely controlled by U(VI) complexation with soil organic matter and not U(VI) bioreduction. Instead, organic-associated U(VI) seems to remain stable under microbially-mediated Fe(III)-reducing conditions. U(IV) (as non-crystalline U(IV)) was only observed at greater depths at the site (>25 cm); the soil here was comparatively mineral-rich, organic-poor, and sulfate-reducing/methanogenic. Furthermore, nanocrystalline UO2, an alternative product of U(VI) reduction in soils, was not observed at the site, and U did not appear to be associated with Fe-bearing minerals. Organic-rich soils appear to have the potential to impede U groundwater transport, irrespective of ambient redox conditions. Highlights: Up to 1600 mg kg −1 U(VI)(s) retained in Needle's Eye soils by organic complexation. Uranyl-organic complexes stable under Fe(III)-reducing conditions. U(VI) reduced to non-crystalline U(IV) under sulfate reducing/methanogenic conditions. U hard to remobilise from Needle's Eye soil.